Avaliação das características de afetividade em crianças e jovens com síndrome de down - Rodrigues, Elaine Custódio (2008)
This work presents the processes and the results of a research concerning the affectivity in children suffering from the Down´s Syndrome (DS). The relevance of the study is justified due to the need of the development of researches, in the area of psychological evaluation of people who suffers from Down´s Syndrome (DS), that are backed by the use of appropriate instruments for such purpose. The thematic discussed focuses the characteristics of the affectivity of children suffering from Down´s Syndrome. Affectivity, conceptually, is considered a wide phenomenon, including several aspects such as emotions, passions, anxiety, anguish, sadness, happiness and even the pleasure sensations and pain. The general objective of the study consisted of investigating the manifestation of the affectivity in children and young with Down´s Syndrome and the parents´ and educators´ perception concerning the expression of the affectivity in the behavior and in the social activities. The specific objectives were: to identify the parents' perceptions about the several manifestations of indicative behaviors of affectivity; to verify in the social atmosphere, outside home, through the teachers' perception, the several forms and intensities of the expression of the affectivity; and, to make possible the use of the technique of Zulliger (Z-test) in people with Down´s Syndrome. 70 (seventy) children and young with Down´s Syndrome participated in the research, in the age group from 04 to 26 years old, which are attended by Institutions of Paraíba and of Rio Grande do Norte. The instruments used were two questionnaires, applied with the parents and teachers, and the projective technique, Z-test, applied, individually, with the children and young with Down´s Syndrome. For analysis of the data of the questionnaires, the program Trideux-Mots was used, with the intention of selecting the main outstanding words for the parents and teachers concerning the expression of the children's affectivity and young with Down´s Syndrome. For so much, it was organized a database that was processed by that program and, soon after, interpreted through the Factorial Analysis by Correspondence (AFC), looking for to clear the modalities of presented answers in an organized way, through a graph. The data of the Z-test were analyzed, taking in consideration the need to characterize the aspects of the affectivity and the elaboration of specific norms for this sample type, through normalized scores. In agreement with the data presented by Tri-deux-Mots, it was observed that in the affective behavior and in the relationship with the other, home and in the school, the children and young with Down´s Syndrome they express your affectivity through positive and negative characteristics, in the same way that any other child that doesn't have to syndrome. The Z-test made possible initial elements to work with that population, however it is necessary that grow other researches with the intention of investigating the reason of the answers they present not the specific categories that you/they are related to the affectivity, since it was well-known the diversity of affective characteristics presented by the researched group